Novel molecular markers of Chlamydia pecorum genetic diversity in the koala (Phascolarctos cinereus) - J. Wallis Marsh; Avinash Kollipara; Peter Timms; Adam Polkinghorne (2011)
Abstract Background Chlamydia pecorum is an obligate intracellular bacterium and the causative agent of reproductive and ocular disease in several animal hosts including koalas, sheep, cattle and goats. C. pecorum strains detected in koalas are genetically diverse, raising interesting questions about the origin and transmission of this species within koala hosts. While the omp A gene remains the most widely-used target in C. pecorum typing studies, it is generally recognised that surface protein encoding genes are not suited for phylogenetic analysis and it is becoming increasingly apparent that the omp A gene locus is not congruent with the phylogeny of the C. pecorum genome. Using the recently sequenced C. pecorum genome sequence (E58), we analysed 10 genes, including omp A, to evaluate the use of omp A as a molecular marker in the study of koala C. pecorum genetic diversity. Results Three genes ( inc A, ORF663, tar P) were found to contain sufficient nucleotide diversity and discriminatory power for detailed analysis and were used, with omp A, to genotype 24 C. pecorum PCR-positive koala samples from four populations. The most robust representation of the phylogeny of these samples was achieved through concatenation of all four gene sequences, enabling the recreation of a "true" phylogenetic signal. Omp A and inc A were of limited value as fine-detailed genetic markers as they were unable to confer accurate phylogenetic distinctions between samples. On the other hand, the tar P and ORF663 genes were identified as useful "neutral" and "contingency" markers respectively, to represent the broad evolutionary history and intra-species genetic diversity of koala C. pecorum . Furthermore, the concatenation of omp A, inc A and ORF663 sequences highlighted the monophyletic nature of koala C. pecorum infections by demonstrating a single evolutionary trajectory for koala hosts that is distinct from that seen in non-koala hosts. Conclusions While the continued use of omp A as a fine-detailed molecular marker for epidemiological analysis appears justified, the tar P and ORF663 genes also appear to be valuable markers of phylogenetic or biogeographic divisions at the C. pecorum intra-species level. This research has significant implications for future typing studies to understand the phylogeny, genetic diversity, and epidemiology of C. pecorum infections in the koala and other animal species.